Change implementation: the association of adaptive reserve and burnout among inpatient medicine physicians and nurses. Issue 5 (3rd September 2018) - Huynh, Christine; Bowles, Darci; Yen, Miao-Shan; Phillips, Allison; Waller, Rachel; Hall, Lindsey; Tu, Shin-Ping
ABSTRACT: Adaptive Reserve (AR) is positively associated with implementing change in ambulatory settings. Deficits in AR may lead to change fatigue or burnout. We studied the association of self-reported AR and burnout among providers to hospitalized medicine patients in an academic medical center. An electronic survey containing a 23-item Adaptive Reserve scale, burnout inventory, and demographic questions was sent to a convenience sample of nurses, house staff team members, and hospitalists. A total of 119 self-administered, online surveys collected from June 2014 to March 2015 were analyzed. Ordinal regression analyses were used to examine the association between AR and burnout. Eighty percent of participants reported either level 1 or 2 burnout. Additionally, 10.9% of participants responded level 0% and 7.6% of participants reported level 3. Participants reporting higher burnout were about three times more likely to report lower AR levels. AR is strongly associated with self-reported burnout by physicians and nurses providing inpatient care at this academic medical center. Growing evidence supports the positive association of AR to successful change implementation in ambulatory settings. Similar studies are needed to determine whether certain levels of AR can predict successful change in hospital settings.